THE POLITICAL MARKETING STRATEGY OF PARTAI SOLIDARITAS INDONESIA IN LEGISLATIVE ELECTION 2019 OF NORTH SULAWESI PROVINCE - Tulung, Lingkan Easter; Lapian, S.L.H.V. Joyce; Tumbel, Altje; Worang, Fredrik G.; Ogi, Imelda W.J. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
Abstract: This research aims to determine PSI’s political marketing strategy in communicating its concept, identity, and work program to the community or its constituents during the political campaign process in the 2019 Legislative Election in North Sulawesi. The research method uses qualitative research methods. To obtain information on research data uses the purposive sampling technique in determining key informants. The data collection techniques are through in-depth interviews, and documentation studies. The results show that in the process of delivering political products, PSI has not been able to balance three political marketing strategies simultaneously. The push-marketing strategy is the most widely used strategy because it is considered the most effective strategy in winning constituents. Through push-marketing strategy PSI introduces candidates and conveys work programs by visiting the community directly or door-to-door and forming discussion forums. Abstrak: Penelitian ini bertujuan untuk mengetahui strategi marketing politik PSI dalam mengkomunikasikan konsep, identitas, dan program kerjanya kepada masyarakat atau konstituennya pada saat proses kampanye politik pada Pemilu Legislatif 2019 di Sulawesi Utara. Metode penelitian menggunakan metode penelitian kualitatif. Untuk memperoleh informasi data penelitian menggunakan teknik purposive sampling dalam menentukan informan kunci. Teknik pengumpulan data melalui wawancara mendalam, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa dalam proses penyampaian produk politik, PSI belum mampu menyeimbangkan ketiga strategi pemasaran politik secara bersamaan. Strategi push-marketing merupakan strategi yang paling banyak digunakan karena dianggap sebagai strategi yang paling efektif dalam memenangkan konstituen. Melalui strategi push-marketing PSI mengenalkan calon dan menyampaikan program kerja dengan mendatangi masyarakat secara langsung atau door to door dan membentuk forum diskusi.